Rancang Bangun Sistem Informasi Inventory Obat Pada Rumah Sakit Jiwa Tampan Berbasis Web - Siti Monalisa; E. Denni Prima Putra; Fitra Kurnia (Program Studi Sistem Informasi, 2018)
Mental Hospital of Tampan is the Pekanbaru City Government Agency which deals with health and psychiatric problems, such as excessive stress, psychiatric disorders, services to people with HIV / AIDS and the service of child development. The mental hospital of Tampan has a large drug supply system with different specifications in the pharmacy department. However, in the process of drug supply, there are still obstacles, namely recording drug supplies and managing transaction data, still using ledgers. In addition, employees often make mistakes in recording and checking as well as inventory of drugs that often occur excess drug orders. The focus of this research is to create a web-based drug inventory information system. System design method uses Object Oriented Analysis and Design (OOAD) method. Drug inventory system employees can manage drug supplies, record, sell, order medicines to suppliers and make reports through a web-based inventory system.Keywords: Inventory system, Mental Hospital of Tampan, OOAD